2020
DOI: 10.1016/j.clml.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT or PET Role in MALT Lymphoma: An Open Issue not Yet Solved—A Critical Review

Abstract: Mucosa-associated lymphoid tissue (MALT) lymphoma involves the mucosa-associated lymphoid tissue potentially arising from any mucosal site, with the stomach as the most common site of involvement. MALT lymphoma is not usually an aggressive disease with a good prognosis except for selected cases. Fluorine-18 ( 18 F) fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) is a noninvasive imaging tool used for staging, restaging, and evaluation of the treatment response in non-Hodgki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 50 publications
(210 reference statements)
0
29
0
Order By: Relevance
“…The applicability of FDG-PET/CT in MALT lymphomas is still controversial due to variable FDG avidity at different MALT locations. Pulmonary and head/neck MALT lymphomas seem to be most FDG avid, and FDG-PET/CT shows higher sensitivities at these regions [ 116 , 117 ]. Since pSS-associated MALT lymphomas frequently develop in the salivary glands and/or lungs, there may be a role for this technique in the detection of lymphomas associated with pSS [ 113 , 118 , 119 ] ( Figure 3 ).…”
Section: Nuclear Medicine Techniquesmentioning
confidence: 99%
“…The applicability of FDG-PET/CT in MALT lymphomas is still controversial due to variable FDG avidity at different MALT locations. Pulmonary and head/neck MALT lymphomas seem to be most FDG avid, and FDG-PET/CT shows higher sensitivities at these regions [ 116 , 117 ]. Since pSS-associated MALT lymphomas frequently develop in the salivary glands and/or lungs, there may be a role for this technique in the detection of lymphomas associated with pSS [ 113 , 118 , 119 ] ( Figure 3 ).…”
Section: Nuclear Medicine Techniquesmentioning
confidence: 99%
“…16 Although combined CT and positron emission tomography (CT/PET) is actually the gold standard for staging purpose in case of primary cutaneous follicle centre lymphoma and primary cutaneous diffuse large B-cell lymphoma, leg type, its introduction as a routine staging test in case of PC-MZL is still debated. 44 Bone marrow biopsy is not mandatory, but it may be useful in the case of single or multiple cell line cytopenia. 22 PC-MZL staging yet requires a careful history and clinical examination and laboratory tests such as: blood count, LDH, Erythrocyte Sedimentation Rate (ESR), C-reactive protein (CRP), beta-2 microglobulin, Serum Protein Electrophoresis (SPE), HIV antibodies, HBV antibodies, AST, ALT, creatinine, amylase, lipase, bilirubin, HCV Antibodies.…”
Section: Patient Managementmentioning
confidence: 99%
“…The staging of marginal zone lymphoma is a challenge with [ 18 F]FDG PET/CT, because marginal zone lymphoma usually does not present with elevated glycolysis and may had heterogeneous metabolic behavior [20,21]. Stollberg S. and the colleagues found that CXCR4 expression was present at a high intensity in 92% of the cases [22].…”
Section: Marginal Zone Lymphomamentioning
confidence: 99%